Prevalence and impact of sleep-related breathing disorder in multiple system atrophy patients: a cross-sectional study and meta-analysis - Wang, Hui; Zhang, Ting; Fan, Wenhui; Xu, Yanming (Frontiers in Neurology, 2024)
Objective Sleep-related breathing disorder (SRBD) is a prevalent non-motor symptom in multiple system atrophy (MSA). However, the reported prevalence of SRBD in MSA from different studies has shown inconsistency. Additionally, only one study has examined the impact of SRBD on both motor and non-motor symptoms in MSA.Methods Cross-sectional study of 66 patients with probable MSA from China. SRBD was ascertained with polysomnography (PSG). All the MSA individuals were assessed using the Epworth Sleepiness Scale (ESS), Unified Multiple-System Atrophy Rating Scale (UMSARS), Hamilton Depression Scale (HAMD), Hamilton Anxiety Scale (HAMA), the Mini-mental State Examination (MMSE), Non-Motor Symptoms Scale (NMSS), and Pittsburgh Sleep Quality Index (PSQI). Moreover, A meta-analysis was conducted by searching studies related to MSA and SRBD in PubMed, Web of Science, Embase, and Cochrane databases. Data were pooled as necessary to calculate prevalence of SBRD with 95% confidence intervals (CI).Our study included 66 patients with MSA, 52 of whom had a diagnosis of SRBD (78.8%). There were no significant differences between the MSA with SRBD and without SRBD groups on the age, sex, disease onset, disease duration, UMSARS I, II, and IV,the NMSS, the HAMA, HAMD , the ESS the FSS, the MMSE,and the PSQI scales. However, MSA patients with SRBD having a significant higher obstructive apnea index and percentage of snoring during sleep than MSA patients without SRBD (10.